Bioinspired sequentially crosslinked nanofibrous hydrogels with robust adhesive and stretchable capability for joint wound dressing. (August 2021) - Zheng, Yuqi; Zhang, Keyan; Yao, Yueming; Li, Xiaoran; Yu, Jianyong; Ding, Bin
Abstract: Despite recent progress in hydrogel wound dressings, joint wound treatment remains an ongoing challenge due to their poor adhesive and stretchable properties. Herein, inspired by protein secretion-curing process of natural marine mussels, an adhesive nanofibrous hydrogel is developed via a sequential crosslinking strategy. Firstly, to avoid uncontrolled self-polymerization of dopamine (DA), DA grafted gelatin (GT) nanofibers are fabricated via electrospinning under pH value around 4. Further, the fibrous hydrogels are in-situ crosslinked under pH value of about 8 to strengthen the intermolecular interaction within fibers. The DA crosslinked GT fibrous hydrogels via Michael addition and Schiff base reaction exhibit superior adhesive and tensile properties which are 1.5 times and 3.1 times higher than those of GT fibrous hydrogels, respectively. The in vitro cytocompatibility tests and in vivo wound healing study further prove that GT grafted DA nanofibrous hydrogels are able to accelerate wound healing. Taken together, we demonstrate a simple and versatile strategy for generating adhesive and stretchable nanofibrous hydrogel, showing a great potential for joint wound care. Highlights: Inspired by protein secretion-curing process of marine mussels, dopamine (DA) sequentially crosslinked gelatin (GT) (GT/EDC–NHS–DA) nanofibrous hydrogels was first developed. GT/EDC–NHS–DA nanofibrous hydrogels possessed exceptional bio-adhesiveness ensuring close and stable wound contact. GT/EDC–NHS–DA nanofibrous hydrogels possessed great tensile mechanical property allowing for 150° frequent facile bending. GT/EDC–NHS–DA nanofibrous hydrogels promoted wound healing significantly with a wound healing ratio of 96% on postoperative day 15.